(untitled) (International Conference on Computers in Education, 2022)
Reading rate is the number of words a user reads per unit of time, also known as reading speed. As online learning has been continuously growing, research on tracking learning behavior is undertaken, and the reading rate was beginning to be applied to measure the learning process. However, current calculating methods are based on the traditional learning environment of a paper-based course, and further research is needed to determine whether they can be used to track students’ learning in an online learning environment and integrate with their online reading habits. To this end, this study proposed a new method based on online learning used to calculate reading rate as a measure to track students’ learning status, after analyzing students’ reading behavior in the e-book learning system. This method not only can identify students with learning difficulties through reading rate outliers, but also provide urgent feedback to students on their reading status.